MEMAHAMI SUBSTANSI MAKNA PERNIKAHAN - Wahyu Ningsih (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2023)
Marriage is the advice of Allah SWT for humans to maintain their existence and to control breeding in a way that is appropriate and according to the norms of religious norms. Men and women have the nature of needing each other. Marriage takes place to achieve the goals of human life and maintain the continuity of its kind. Marriage is one of the most important worship in the association of Islamic religious communities and society. Marriage is not only a way to build a household and continue the descent. Marriage is also seen as a way to increase ukhuwah Islamiyah and expand and strengthen the relationship between humans